An analysis of the effect quality patient satisfaction services in hospital inpatient installation Aek Canopan area - Ayu Hasanah Panjaitan; Ermi Girsang; Maya Sari Mutia (Jurnal Ekonomi, 2024)
With the increasing number of hospitals, each hospital must have its strategy to persuade patients to want to use the hospital's services, one way is by improving the quality of service. This paper describes a quality of services provided is one of the factors for patients to choose a place for treatment. In the health industry, service quality is very important in attracting patients' interest in using the health services offered to increase patient satisfaction. Apart from that, hospitals must also maximize their marketing mix strategy, which is a strategy that includes several elements, namely product, price, promotion, location, people, physical evidence, and process. All elements must be maximized to obtain optimal results. Simultaneously or together, service quality with the dimensions of responsiveness, empathy, and tangible influence patient satisfaction in Class I, II, and II Inpatient Installations at Aek Kanopan Regional General Hospital. Simultaneously or together, the marketing mix with dimensions, namely type of service, service location, promotion, health personnel, physical appearance, service process, and hospital performance, each influences patient satisfaction in Class I, II, II Hospital Inpatient Installations General Aek Kanopan Region, while the dimensions of reliability and assurance have no effect.